2013
DOI: 10.2135/cropsci2012.03.0157
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Gain × Management Interactions in Soybean: I. Planting Date

Abstract: Planting date is a commonly manipulated management practice in soybean [Glycine max (L.) Merr.] production; however, the impacts of past and ongoing agronomic improvements, such as earlier planting, on genetic yield improvement and associated changes in seed protein and oil have not been evaluated. The objectives of this study were to determine if a 30‐d difference in planting date affected measured rates of genetic improvement in (i) yield, (ii) seed mass, and (iii) seed protein and oil in the midwestern Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
96
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 28 publications
12
96
1
2
Order By: Relevance
“…Sowing date is the management factor with the greatest impact on soybean yields in the US Corn Belt (Bastidas et al, 2008;De Bruin and Pedersen, 2008;Villamil et al, 2012;Rowntree et al, 2013). Linear regression analysis was used in the present study to assess the impact of sowing date on inter-annual yield variation in irrigated and rainfed soybean.…”
Section: Assessment Of Explanatory Factors For Variation On Soybean Smentioning
confidence: 99%
“…Sowing date is the management factor with the greatest impact on soybean yields in the US Corn Belt (Bastidas et al, 2008;De Bruin and Pedersen, 2008;Villamil et al, 2012;Rowntree et al, 2013). Linear regression analysis was used in the present study to assess the impact of sowing date on inter-annual yield variation in irrigated and rainfed soybean.…”
Section: Assessment Of Explanatory Factors For Variation On Soybean Smentioning
confidence: 99%
“…Rowntree et al (2013) Genetic improvements of soybean have increased yield through changes in seed quality and physiology across release years. Soybean yield and oil increased as protein concentration decreased with the advancement of soybean cultivars over time (Rowntree et al, 2013;Wilcox et al, 1979).…”
mentioning
confidence: 99%
“…Rowntree et al (2013) Genetic improvements of soybean have increased yield through changes in seed quality and physiology across release years. Soybean yield and oil increased as protein concentration decreased with the advancement of soybean cultivars over time (Rowntree et al, 2013;Wilcox et al, 1979). Boerma (1979), Morrison et al (2000), and Voldeng et al (1997) reported seed mass was not well correlated with cultivar release year, but Specht and Williams (1984) noted an annual increase in seed mass (0.10 g per 100 seeds).…”
mentioning
confidence: 99%
See 2 more Smart Citations